Rethinking The Feasibility of Pancasila as a Scientific Paradigm - Taufiqurrahman Taufiqurrahman (Badan Pembinaan Ideologi Pancasila, 2023)
Some academics and state officials in Indonesia argue for the adoption of Pancasila as a scientific paradigm for the country's scientific endeavours. They believe that using Pancasila as a foundation could give Indonesian science a distinct and unique character. However, this article seeks to reevaluate the feasibility of Pancasila as a scientific paradigm. By reviewing the literature on Pancasila and the philosophy of science, it arrives at the conclusion that Pancasila cannot serve as a scientific paradigm, either in a narrow or comprehensive sense. Two primary reasons support this conclusion. Firstly, Pancasila lacks the necessary characteristics of a well-established scientific achievement. As a result, it cannot function as a scientific paradigm in the narrow sense defined by Kuhn. Secondly, Pancasila carries theological baggage that surpasses science’s capacity to accommodate it. This aspect prevents Pancasila from becoming a comprehensive scientific paradigm. Consequently, I propose that Pancasila is more suitable as an axiological basis for science, rather than a scientific paradigm. Unlike a scientific paradigm, this axiological foundation does not fall within the epistemic scope of science.